Hypoxia and its feedback response to algal blooms and CH4 emissions in subtropical reservoirs - Ji, Daobin; Han, Yanxing; Long, Lianghong; Xin, Xiaokang; Xu, Hui; Qiu, Siqian; Meng, Jianghuai; Zhao, Xingxing; Huang, Yanan; Liu, Defu (Frontiers in Ecology and Evolution, 2024)
Anthropogenic nutrient input stimulates surface eutrophication and algal blooms and thus exacerbates oxygen depletion and hypoxia in aquatic ecosystems. However, existing studies have paid little attention on the understanding of the feedback relationships among oxygen consumption, algal succession and greenhouse gas effect after river damming, particularly in Three Gorges Reservoir. This field work investigated the thermal stratification, water quality and phytoplankton in four tributaries (Pengxi Bay (PXB), Daning Bay (DNB), Shennong Bay (SNB), and Xiangxi Bay (XXB)) of the Three Gorges Reservoir (TGR) in spring (April 25-28, 2022), and explored the drivers of hypoxia and its feedback response to algal blooms and methane (CH4) emissions. The results showed that during the observation period, DO, thermal stratification, and algal blooms were more severe in PXB. The high Chemical Oxygen Demand (CODMn) (11.27 mg·L-1) and Dissolved Organic Carbon (DOC) content (7.56 mg·L-1) in PXB were the main causes of the progressive hypoxia. Furthermore, stronger density stratification in PXB inhibited the vertical supply of DO and accelerated bottom hypoxia. But the downslope density current replenished bottom DO in the upper reaches of the DNB, SNB, and XXB. The CH4 concentration was generally higher in hypoxia zone, especially in where cyanobacteria are the dominant species (eg., PX03 and PX04). Dam construction led to the succession of algal-dominant species, exerting a significant influence on the river carbon cycle. The expansion of cyanobacterial blooms and the consequence of metabolic substrates increase are gradually increasing oxygen deprivation, even hypoxia, and enhancing CH4 production in rivers. These findings suggest that the succession of algal-dominant species caused by river damming has a pronounced positive feedback effect on reservoir hypoxia processes and greenhouse effect.